Modification of Monetite Formation by Controlling of Phosphoric Acid Addition - Herlina Damayanti; Karlina Noordiningsih; Kristanto Wahyudi (Jurnal Keramik dan Gelas Indonesia, 2020)
Development of synthetic biomaterials has been done to repair bones and teeth damaged. Monetite is a biomaterial currently being developed for tissue engineering especially bone and dental applications because it has superior osteoconductive, biodegradable and regeneration properties. This research successfully produced the mineral monetite by modification of wet precipitation method with controlling the rate of phosphoric acid addition to calcium hydroxide. The reaction temperature is around 30oC - 65oC and the pH of the solution about 3. The final product from this precipitation process was characterized by XRD for testing mineral content, XRF for testing chemical content, and also SEM for knowing the morphology of product. The results showed that the optimal condition for monetite formation was D2, with controlling of the phosphoric acid rate ¼ mL/second for 2 hours and increased to ½ mL/second for 1 hour. The reaction temperature in the range 34 oC - 50oC and pH 3. The diffraction pattern from XRD test results showed monetite peaks at the following 2θ angle: 13.1; 26.4; 30.2; and 32.9 with the highest intensity (D2) is 4500. Also, the morphology of the crystalline structure approximates the actual monetite crystal, which is like a plate with a width of a particle about 1-3 µm. Thus, the results of this research provide an opportunity further research of the application monetite for tissue and dental engineering materials